2012
DOI: 10.1200/jco.2011.39.9782
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Phase III Study of Gemcitabine or Erlotinib Maintenance Therapy Versus Observation, With Predefined Second-Line Treatment, After Cisplatin-Gemcitabine Induction Chemotherapy in Advanced Non–Small-Cell Lung Cancer

Abstract: Gemcitabine continuation maintenance or erlotinib switch maintenance significantly reduces disease progression in patients with advanced NSCLC treated with cisplatin-gemcitabine as first-line chemotherapy. Response to induction chemotherapy may affect OS only for continuation maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
2
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(160 citation statements)
references
References 32 publications
(16 reference statements)
5
136
2
5
Order By: Relevance
“…In the present study, the survival of all consecutive NSCLC patients in daily practice was evaluated, therefore, the study included ʻunfitʼ patients, who are usually excluded from clinical trials. However, it was notable that the OS time in these patients was not shorter than that observed in recent clinical trials (25)(26)(27)(28)(29)(30). In addition, in the present patients treated with platinum and pemetrexed, the OS time was as long as that observed in the PARAMOUNT trial (16.9 months) (31).…”
Section: Recently Mandrekar Et Alcontrasting
confidence: 46%
“…In the present study, the survival of all consecutive NSCLC patients in daily practice was evaluated, therefore, the study included ʻunfitʼ patients, who are usually excluded from clinical trials. However, it was notable that the OS time in these patients was not shorter than that observed in recent clinical trials (25)(26)(27)(28)(29)(30). In addition, in the present patients treated with platinum and pemetrexed, the OS time was as long as that observed in the PARAMOUNT trial (16.9 months) (31).…”
Section: Recently Mandrekar Et Alcontrasting
confidence: 46%
“…[30] Moreover, gemcitabine maintenance treatment was only a useful treatment option for lung cancer patients with good performance status and patients who demonstrated an objective response to platinum-gemcitabine. [31] So, possible response rate is low and benefit is insufficent for patients who presented stable disease following the first-line chemoterapy for lung cancer. Thus, parameters predicting the benefit of maintenance therapy gain importance for the proper selection of maintenance treatment, best supportive care or second-line chemotherapy for many cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Other trials have shown improvements in PFS (but not OS) for maintenance. Docetaxel (Fidias et al [15]) or gemcitabine (CECOG and IFCT-GFPC 0502 trials [36,37]) could also be considered, especially for patients with squamous NSCLC tumors.…”
Section: Optimal Maintenance Strategy: Which Is Best?mentioning
confidence: 99%